Síntese e avaliação farmacológica de novos compostos híbridos úteis para tratamento das complicaçôes da anemia falciforme - Melo, Thaís Regina Ferreira de [UNESP] (2014)
Sickle Cell Anemia is a genetic blood disease in which there is a mutation in the β-hemoglobin gene. This mutation promotes polymerization of hemoglobin molecules that change the structure of the erythrocyte cytoskeleton promoting sickling of the cell. Moreover, there is increased adhesion of blood cells in the vessel contributing to the increasement of the vaso-occlusive process, the main characteristic of the disease. It is further known that the chronic inflammation associated with the disease contributes to a number of complications and among the process responsible for this proinflammatory cytokine is TNF-α, which is an important target for therapeutic intervention. Hydroxyurea (HU) is the only available drug for treatment and its beneficial effects are associated with the same capacity biotransformation of nitric oxide. The NO plays beneficial effects such as vasodilation, inhibition of platelet aggregation and production of fetal hemoglobin (Hb F), latter has the function of decreasing polymerization of hemoglobin. In this context, continuing the research line that aims at planning , synthesis and pharmacological evaluation of new prototypes drug candidates for the treatment of sickle cell anemia complications, in this work have synthesized a series of four new hybrid compounds ( I- IV) containing the phtalimide (TNF-alfa inhibitory subunit) and furoxan subunits ( nitric oxide donors) according to structural design. The compounds were presented as NO donors. Compounds I-IV were shown to be inhibitors of TNF-α in the immunoassay of this cytokine assay and the compound IV is the most promising inhibiting between 65% in smaller concentrations than the other. In the assay of ADP-induced platelet aggregation, compounds III and IV were able to inhibit platelet aggregation sigficantily. In addition, the compound I after 72 hours was able to increase the gene expression of gamma globin approximately two times the control, at a ...